Câncer de pulmão em não tabagistas - Baú, Renata (2020)
Introduction Although lung cancer is strongly related to smoking, approximately 20% of patients who have never smoked develop lung cancer. This proportion varies according to geographic location, sex and exposure to other risk factors. Still, some numbers study this group, which starts the epidemiological survey to provide data that can help in a better understanding of this condition. This study aims to analyze patients who were operated on for lung cancer with curative intent in a thoracic surgery center in Rio Grande do Sul, in the period from 2012 to 2018. The data analyzed were detailed by the research studied, characteristics cases of diseases in these cases, type of surgery performed and complications of surgical treatment in smokers and non-smokers. Methodology Cross-sectional design for data analysis of patients with lung cancer examined surgically with curative intent at Irmandade Santa Casa de Misericórdia in Porto Alegre. Data listed in the institution's database were collected and data insufficiently presented were excluded. Results Sample consisted of 981 patients. Of these, 208 (21.2%) didn't have history of exposure to smoking, with 773 (78.8%) being active smokers, passive or ex-smokers. Among non-smokers, most were women (73.1%). Active smokers most often had a history of weight loss before surgery (p = 0.005). Lung function was better among nonsmokers (p <0.001). Non-smokers, adenocarinoma was the most frequent tumor (67.3%), followed by neuroendocrine carcinoma (18.3%) and squamous cell carcinoma (9.1%) In the present study, male gender, weight loss, smoking and need for pneumonectomy were factors associated with a higher number of complications. Conclusion In the analysis of patients undergoing lung cancer, 208 (21.2%) were not smokers, in which adenocarcinoma was the most common histological type. These patients, unlike the cases in smokers, were mostly female, younger, with better spirometric results and with lower rates of postoperative complications.